Investigating antioxidant activity of carotenoid compound from Paracoccus haeundaensis SAB E11 at the cellular level in Schizosaccharomyces pombe ARC039 yeast model - Hermawaty Abubakar,, Rika Indri Astuti,, Irmanida Batubara,, Sri Listiyowati, Aris Tri Wahyudi (Journal of Applied Pharmaceutical Science, 2025)
This study aimed to investigate the presence, characterization, and antioxidant properties of carotenoid compounds at the cellular level in the bacteria Paracoccus haeundaensis SAB E11. Furthermore, carotenoid synthesis was determined based on the presence of the crtY gene. Characterization of the carotenoid isolated was performed through thin-layer chromatography (TLC), UV-Vis spectrum, high-performance liquid chromatography (HPLC), and Fourier-transform infrared spectroscopy (FTIR). Meanwhile, cellular antioxidant activity was examined using 2,2-diphenyl-1-picryhydrazyl (DPPH) radicals and the organism model yeast Schizosaccharomyces pombe ARC039. The results showed that P. haeundaensis SAB E11 had a band on the chromatogram at 163 bp, representing 54 amino acid residues of lycopene β-cyclase crtY. TLC, UV-Vis, HPLC, and Fourier transform infrared spectroscopy (FTIR) analyses confirmed carotenoid presence, while the DPPH radicals assay identified antioxidant activity with an IC50 value of 203.90 ± 3.12 μg.ml−1 At the cellular level, carotenoid concentrations of 28 μg.ml-1 and 56 μg.ml-1 could enhance the stress tolerance phenotype of S. pombe ARC039 against 2 mM H2O2. Strong induction of mitochondrial activity was obtained following treatment with the 28 μg.ml-1 concentration. After H2O2 treatment, there was a 3.18 and 2.55-fold increase in the relative expression of catalase (ctt1) and superoxide dismutase (sod2) genes of S. pombe ARC039, respectively. These data showed that P. haeundaensis SAB E11 produced carotenoids with potential antioxidant capabilities manifested at the cellular level by inducing an adaptive oxidative response and mitochondrial activity, as well as increasing the expression of ctt1 and sod2 genes.
Keywords: Antioxidant, carotene, lycopene β-cyclase crtY, P. haeundaensis SAB E11, S. pombe ARC039